Imaging of native transcription factors and histone phosphorylation at high resolution in live cells - Conic, Sascha (2018)
Fluorescent labeling of endogenous proteins for live-cell imaging without exogenous expression of tagged proteins or genetic manipulations has not been routinely possible. We describe a simple versatile antibody-based imaging approach (VANIMA) for the precise localization and tracking of endogenous nuclear factors. Our protocol can be implemented in every laboratory allowing the efficient and nonharmful delivery of organic dye-conjugated antibodies, or antibody fragments, into different metazoan cell types. Live-cell imaging permits following the labeled probes bound to their endogenous targets. By using conventional and super-resolution imaging we show dynamic changes in the distribution of several nuclear transcription factors (i.e., RNA polymerase II or TAF10), and specific phosphorylated histones (γH2AX), upon distinct biological stimuli at the nanometer scale. Hence, considering the large panel of available antibodies and the simplicity of their implementation, VANIMA can be used to uncover novel biological information based on the dynamic behavior of transcription factors or posttranslational modifications in the nucleus of single live cells.